2010
DOI: 10.1007/s11104-010-0665-y
|View full text |Cite
|
Sign up to set email alerts
|

Dry matter and nitrogen accumulation and partitioning in rice (Oryza sativa L.) exposed to experimental warming with elevated CO2

Abstract: Effects of elevated CO 2 concentration ([CO 2 ]) and air temperature (T air ) on accumulation and intra-plant partitioning of dry matter (DM) and nitrogen in paddy rice were investigated by performing a pot experiment in six natural sunlit temperature gradient chambers (TGCs) with or without CO 2 fumigation. Rice (Oryza sativa L.) plants were grown in TGCs for a whole season under two levels of [CO 2 ] (ambient, 380 ppm; elevated, 622 ppm) and two daily T air regimes (ambient, 25.2°C; elevated, 27.3°C) in spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 30 publications
(64 reference statements)
6
52
0
2
Order By: Relevance
“…The latter likely supported our result that at full heading stage tiller number showed the lack of response to elevated [CO2]. This was probably attributed to the strong carbon (C) and nitrogen (N) sink of the vigorous reproductive tiller, which may have depressed the supply of C and N to the smaller tillers (Daepp et al, 2001) (Oh-e et al, 2007;Kim et al, 2011). However, the higher-Ta-induced increase in tiller was not always linked to the increase in final tiller number at harvest (Oh-e et al, 2007).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The latter likely supported our result that at full heading stage tiller number showed the lack of response to elevated [CO2]. This was probably attributed to the strong carbon (C) and nitrogen (N) sink of the vigorous reproductive tiller, which may have depressed the supply of C and N to the smaller tillers (Daepp et al, 2001) (Oh-e et al, 2007;Kim et al, 2011). However, the higher-Ta-induced increase in tiller was not always linked to the increase in final tiller number at harvest (Oh-e et al, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…However, this does not mean that leaf angle would also be unchanged. Assuming that leaf angle is in inverse relation to leaf nitrogen (N) content (Chen et al, 2003), rice crops grown in elevated [CO2] will be expected to have more erect leaves than those in ambient [CO2] because rice plants showed a significant reduction in leaf N content at elevated [CO2] (Kim et al, 2003(Kim et al, , 2011Seneweera et al, 2011;Yang et al, 2007). On the other hand, elevated Ta significantly increased the fraction of LAI distributed into the upper layer (75-90 cm), but decreased that distributed into the lower layer (45-60 cm) both under ambient and elevated [CO2] (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Neste processo, um grupo carboxila (COOH) e um grupo amina (NH 2 ) são adicionados às cadeias carbonadas dos carboidratos, consumindo, entre outros compostos e enzimas, o nitrogênio (N). A quantidade de nitrogênio presente no interior das folhas para este metabolismo é, portanto, outro fator limitante para a manutenção das altas taxas fotossintéticas em elevadas concentrações de CO 2 atmosférico em curto prazo (KIM et al, 2011). O aumento da taxa fotossintética, juntamente com a maior produção de carboidratos, fará com que a demanda de N seja bastante elevada e este maior consumo de N, consequentemente, ocasionará uma potencial deficiência de N nas folhas (Figura 1).…”
Section: Suprimento Da Demanda De Nitrogêniounclassified
“…Apesar do aumento da taxa fotossintética em elevadas concentrações de CO 2 , observa-se que este efeito não é constante ao longo do ciclo das culturas e muitas vezes não resulta em aumento de produtividade (ARENQUE et al, 1014;KIM et al, 2011;CALIMAN et al, 2009;YANG et al, 2006), por ser afetado pelo processo da aclimatação. A aclimatação das plantas à elevada concentração de CO 2 atmosférico consiste em uma série de alterações no metabolismo vegetal em diferentes níveis de organização (desde molecular e bioquímico até anatômico e morfológico).…”
Section: Introductionunclassified
“…They reported that the growth characteristics -root and shoot lengths, root volume, root: shoot ratios, leaf area, dry weights of different plant parts, leaf area duration and crop growth rate increased significantly with 550 ppm and 700 ppm of CO 2 levels. Kim et al (2011), in a pot experiment studied the effects of elevated CO 2 concentration on accumulation and intra-plant partitioning of dry matter (DM). Overall, total grain DM increased with elevated CO 2 by 69.6 % and shoot DM increased 46.6 % in rice.…”
Section: Variation In Response For Phenotypic Traitsmentioning
confidence: 99%